Games and Fiction: Partners in the Evolution of Culture. Issue 1 (2nd January 2017) - Kretchmar, Scott
Abstract: In this essay, I argue that the time is right in the philosophy of sport to follow the lead of systems thinking and emphasize the contextual embeddedness of sport, not its distinctive characteristics, least of all any claims for metaphysical independence. Accordingly, I analyze similarities between two cultural conventions—namely, literature (in particular fiction) and games—through the lens of evolution. I argue that common roots can be observed in games and fiction when looking at them structurally, semantically, and socially. I suggest that both games and fictional storytelling were adaptive in similar ways and that both preceded what is arguably the capstone cultural achievement of formal language.